A review of cloud computing implementation in ASEAN countries - Asyran Zarizi, Abdullah; Wan Isni Sofiah, Wan Din; Zalili, Musa; Razulaimi, Razali (IOP Publishing, 2020)
Cloud Computing is a technology that allows services of the communication, file transfer, infrastructure and platform usage to the user through the internet. In the era of globalisation, each of the countries raced to growth cloud technology as the main part of their industrial development. Similarly, with ASEAN countries, they start using cloud technology as a core part of the industrial revolution 4.0 (IR 4.0) to increase their economy and raise productivity. ASEAN already started using cloud computing, but some country has slow progress due to several challenges such as the broadband quality, lack of cloud knowledge and security issues. They require some strategies to address this problem in order to prove the ASEAN can be competitive in the use of technology as it can open up better industrial opportunities. This article reviews the published literature on the implementation of cloud computing in ASEAN. The author systematically analysed a total of 37 selected articles. There were 22 of the articles selected through restrictive search criteria while the other 15 were selected based on unrestrictive search criteria. The review shows the cloud implementation, expose the benefit and challenge to grow a cloud computing in general, and focusing the challenge of ASEAN in cloud computing development. This paper concludes with some recommended future works to construct the theory and perform empirical research.